Portable three-wavelength standard for energy unit of pulse laser radiation - Owsik, J.; Zarwalska, A.; Janucki, Ja.; Samoylov, V.B. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
New instrument for applications in metrological measurements of laser pulse energy is presented. Due to its parameters, it can be used as a standard for energy unit of pulse laser radiation. The instrument consists of a control unit, three different sources of laser radiation, two detectors of optical signal, and a laptop. The whole system can be easily transported enabling one to perform measurements in situ, at customers, and not only in laboratory conditions. A method of measurements used in the standard operation is described. Main characteristics of the standard are shown. Methods enabling calculations of measurement uncertainties during laser energy meter calibration by means of our standard are also presented.